Nigeria's economic relations with the major developed market-economy countries 1960-1985 - Akindele, R. A.; Ate, Bassey E. (Lagos : Nigerian Institute of International Affairs in co-operation with Nelson Publishers, Nelson Publishers, 1988)
The book analyses Nigeria's external relations with concentrations on the conduct of the country's political and diplomatic relations with other states in the international system since 1960 with a little attention paid o the expanding cobweb of country's international economic transactions.
Includes bibliographical references.
opc10/1/17
Loans
Keywords: International economic co-operation; International economic relations; International economics; Nigeria